2022
DOI: 10.1158/1055-9965.epi-22-0601
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal and Other Oral Bacteria and Risk of Lung Cancer in the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background: Evidence suggests that periodontal disease is associated with increased lung cancer risk, but whether periodontal pathogens are explanatory is unknown. We prospectively studied associations of pre-diagnostic circulating antibodies to oral bacteria and of periodontal bacteria in subgingival plaque with lung cancer. Methods: We included 4,263 cancer-free participants in the Atherosclerosis Risk in Communities study with previously measured serum IgG antibodies to 18 oral bacteria. In 1,287 participan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…A greater understanding is necessary as several studies have linked oral diseases to different systemic diseases 27 28. An association between lung cancer and periodontal and other oral bacteria has been studied in the Atherosclerosis Risk in Communities Study, which investigated IgG antibodies to 18 oral bacteria in 1287 participants 29. In a 17.5-year follow-up study, the authors found bacteria of the orange complex to be positively associated with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A greater understanding is necessary as several studies have linked oral diseases to different systemic diseases 27 28. An association between lung cancer and periodontal and other oral bacteria has been studied in the Atherosclerosis Risk in Communities Study, which investigated IgG antibodies to 18 oral bacteria in 1287 participants 29. In a 17.5-year follow-up study, the authors found bacteria of the orange complex to be positively associated with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…naeslundii was inversely associated with overall cancer mortality. In a recent prospective cohort study on lung cancer risk ( 10 ), antibodies against P . intermedia and P .…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis have been linked to increased risk of oropharyngeal cancers and mortality ( 8 , 9 ). In a recent cohort, a positive association was observed between antibodies to Prevotella intermedia and Porphyromonas nigrescens and risk of lung cancer (per interquartile range: hazard ratio = 1.15, 95% confidence interval [CI] = 1.04 to 1.26) ( 10 ).…”
mentioning
confidence: 99%
“…In addition, statistical analysis showed a correlation between the presence of F. nucleatum and the risk of developing systemic cancers, especially lung cancer [ 82 ]. In a manner akin to the observations made regarding P. gingivalis , there exists a positive correlation between serum levels of IgG antibodies targeting F. nucleatum and the occurrence of lung cancer [ 71 ]. This alignment between the antibody levels and lung cancer underscores a potential association between F. nucleatum and the pathogenesis of lung cancer, meriting further investigation.…”
Section: Specific Respiratory Diseases Relating To P Gingiv...mentioning
confidence: 96%
“…Furthermore, lung cancer patients with P. gingivalis infection also had significantly lower survival rates and median survival times [ 69 ]. Moreover, through the assessment of IgG antibodies specific to P. gingivalis within the serum of lung cancer patients, a positive correlation has been established between the levels of these antibodies and the susceptibility to developing lung cancer when contrasted with a cohort of healthy controls [ 70 , 71 ]. This intriguing link between the level of antibodies targeting P. gingivalis and the associated risk of lung cancer highlights a potential role of P. gingivalis in lung cancer pathogenesis.…”
Section: Specific Respiratory Diseases Relating To P Gingiv...mentioning
confidence: 99%